2020
DOI: 10.3390/cancers12020448
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age-Related Genetic Differences on the Therapeutic Outcome of Papillary Thyroid Cancer

Abstract: The incidence of papillary thyroid carcinoma (PTC) has been increasing worldwide. PTC is the most common type of differentiated thyroid cancer and usually shows good prognosis. However, some PTC is driven to advanced stage by epithelial-mesenchymal transition (EMT)-mediated drug resistance, which is particularly noticeable in pediatric patients. There are limited options for systemic treatment, necessitating development of new clinical approaches. Here, we aimed to clarify genetic differences due to age of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…Therefore, models are necessary to predict patients with TC at high risk for bone metastases, and to provide early attention and screening. In previous studies, 26–29 age has been demonstrated to have an impact on the prognosis of TC patients, and it has been reported that the risk of DM was significantly reduced in younger TC patients compared with older patients 30 . And we found that age was also an important feature influencing BM in our study.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, models are necessary to predict patients with TC at high risk for bone metastases, and to provide early attention and screening. In previous studies, 26–29 age has been demonstrated to have an impact on the prognosis of TC patients, and it has been reported that the risk of DM was significantly reduced in younger TC patients compared with older patients 30 . And we found that age was also an important feature influencing BM in our study.…”
Section: Discussionsupporting
confidence: 72%
“…We showed that Lenvatinib promoted the apoptosis pathway in a concentrationdependent manner and that LR increased the anti-apoptotic effects of Lenvatinib in both SMMC-7721 and Huh7 cells, which implies that LR formation is probably associated with inhibition of the apoptosis pathway. Several other studies have shown that the apoptosis pathway may be activated after Lenvatinib stimulation [20][21][22]. Although some studies reported that Lenvatinib did not dose-dependently suppress tumor growth and apoptosis in cell lines [14], it should be noted that instant culturing with Lenvatinib may not be enough to affect the apoptosis pathway [20].…”
Section: Discussionmentioning
confidence: 97%
“…MT1JP has previously been reported to act as a tumor suppressor in breast and bladder cancer [23,24] and it has been reported that MT1JP may inhibit the proliferation, invasion and migration of tumor cells [25,26]. Zhu et al reported that MT1JP could inhibit the tumorigenesis and enhance the cisplatin sensitivity of breast cancer cells through competitively binding to miR-24-3p [22]. In this study, overexpression of MT1JP in breast cancer cells significantly inhibited their proliferation and enhanced their cisplatin sensitivity, which seems to be discordant with our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After transfer process, the primary antibodies against CHOP purchased from Cell Signaling Technology; Danvers, MA, USA, Bcl-2, cytochrome c , Snail1, Zeb1, and histone H2B purchased from Abcam; and PKC, MEK, p-ERK, ERK, and β-actin purchased from Santa Cruz Biotechnology, Santa Cruz, CA, USA were maintained overnight at 4 °C. As detailed in previous research [ 70 ].…”
Section: Methodsmentioning
confidence: 99%